Arabidopsis SERK1 and 2 Regulate Anther Development as Co-Receptors of EMS1 - (:unkn) unknown (My University, 2013)
In flowering plants, male reproductive cell differentiation, one of the most critical events in the early stage of sexual reproduction, occurs during anther development. In the model plant species Arabidopsis, anther development in each lobe results in the differentiation of five highly organized cell layers with unique identities, including the central male reproductive cells and four somatic cell layers. These features make the Arabidopsis anther an ideal system in which to investigate the mechanisms of cell fate determination and differentiation. Previous studies have demonstrated that a leucine-rich repeat receptor-like kinase (LRR-RLK), EXCESS MICROSPOROCYTES1 (EMS1/EXS1), plays an important role during Arabidopsis anther development. In this study, we provided both genetic and biochemical evidence showing that two additional LRR-RLKs, SERK1 and SERK2, are also involved in the regulation of anther cell development as co-receptors of EMS1. In our genetic studies, based on a recently identified weak allele of EMS1, ems1-2, we first showed that EMS1 and SERK1/2 interact with each other genetically, as indicated by the sterile phenotype of ems1-2 serk1-1double mutant. We then showed that EMS1 and SERK1/2 function in the same genetic signaling pathway. The full function of EMS1 is dependent on SERK1/2 expression, which suggests that SERK1/2 may work as co-receptors of EMS1. We also used complementation experiments to show a partial functional redundancy between SERK1 and SERK2. Moreover, SERK1 seems to be more important functionally during Arabidopsis anther development due to its biochemical nature, as reflected by its stronger autophosphorylation level compared with SERK2 during the in vitro kinase assay. In biochemical studies focusing on SERK1 and EMS1, we showed that EMS1 specifically interacts with SERK1 in the bimolecular fluorescent complementation (BiFC) assays using Arabidopsis protoplasts. We also made truncated versions of EMS1 and SERK1 in order to narrow down the particular regions responsible for the interaction. In addition, we demonstrated the significance of EMS1 phosphorylation during the interaction of EMS1 and SERK1. We showed that transphosphorylation between EMS1 and SERK1 enhanced the phosphorylation levels of both proteins. Also, multiple serines and threonines were detected as phosphorylation sites in our in vitro mapping effort within the kinase domain of EMS1. In summary, this study provides both genetic and biochemical evidence suggesting that SERK1/2 regulate Arabidopsis anther cell development as co-receptors of EMS1. Phosphorylation of multiple serine/threonine residues in the EMS1 kinase domain is critical for the physiological function of EMS1.